Encyclopedia of communication theory - Littlejohn, Stephen W.; Foss, Karen A.; Gale Group (Thousand Oaks, Calif. Sage, 2009)
Provides students and researchers with a comprehensive overview of contemporary communication theory. Entries address topics related not only to paradigms, traditions, and schools, but also metatheory, methodology, inquiry, and applications and contexts.
v. 1. A - I -- v. 2. J - Y.
Electronic reproduction.
Keywords: Communication -- Encyclopedias; Information theory -- Encyclopedias; Linguistics -- Encyclopedias; Electronic books